Pharmacokinetics and Tissue Distribution of Minocycline following Intravenous Administration in Rabbits. (4th October 2017) - Petraitis, Vidmantas; Petraitiene, Ruta; Maung, Bo Bo Win; Nolan, Tom G; Griffith, David C; Dudley, Michael N; Walsh, Thomas J
Abstract: Background: Multidrug-resistant A. baumannii, S. maltophilia, and B. cepacia have been identified as priority organisms of infectious diseases and as important causes of refractory pneumonia. These three pathogens require urgent attention for development of new therapeutic options. However, few if any novel antibacterial antibiotics against these organisms are available. In order to understand the impact of minocycline dose on plasma and tissue distribution, we conducted a detailed pharmacokinetic study in rabbits. Methods: NZW rabbits received a single dose of minocycline as an IV infusion with serial plasma sampling over 24 hours. During the second stage, minocycline was administered Q12h for 6 days at 6, 12, 24, 48, or 96 mg/kg with serial plasma sampling and tissue recovery on day 7. Plasma and tissue concentrations were determined by LC/MS/MS. Minocycline pharmacokinetic parameters were estimated using standard non-compartmental methods. Results:   Conclusion: These data suggest that administration of minocycline in rabbits should produce levels of drug that would be active against target organisms in plasma, tissues, and other body fluids. Disclosures: T. G. Nolan, The Medicines Company: Employee, Salary. D. C. Griffith, The Medicines Company: Employee, Salary. M. N. Dudley, The Medicines Company: Employee, Salary. T. J. Walsh, Astellas, Actavis, Contrafect, Drais, iCo, Novartis, Methylgene, Pfizer, Sigma-Tau: Consultant, Consulting fee. Astellas, Actavis, Merck, Novartis, Phizer, Sctnexis, Tetraphase, The Medicines Company, Theravance: Grant Investigator, Research grant.